Saúde do trabalhador : estratégias do trabalho interdisciplinar com foco na gestão, saúde e trabalho - Rosa, Kyriê Machado da (2014)
This paper presents a study on how developed the interdisciplinary work of health professionals of a Federal Institution of Public Higher Education in Porto Alegre / Rio Grande do Sul who work directly with workers made redundant because of illness during the period set between 2013 and 2014. O study is subsidized by the dialectical-critical method of Marxist inspiration. This is a qualitative research, in which we use techniques such as semi-structured interviews with technical workers in the health field working at a Health Division and users of this service workers, in addition to document analysis. We discuss the impact of work on workers' health, their metamorphosis, its present meaning for workers, but also the strategies developed by a health team that institution to better meet the demands presented by users of the service. We reflect on the contributions that the practice of interdisciplinary work can generate both for workers who perform this way of thinking and do the job, as the subjects who experience this experience during the sessions and monitoring this health team. We highlight the collective work as a coping tool and autonomy of the working class facing the dilemmas posed by the world of work.